Development and research of the method for propane-butane gas conversion into methanol - Целищев, Алексей Борисович; Лория, Марина Геннадиевна; Елисеев, Пётр Йосипович; Носач, Владимир Александрович; Иджагбуджи, Айодежи Адебайо; Федотов, Роман Николаевич (Eastern-European Journal of Enterprise Technologies, 2015)
The schematic diagram and the physicochemical study of the process of propane-butane gas conversion into methanol in the presence of hydrogen peroxide solution were proposed. In general, the process of methanol formation is described in the reaction: (C3H8+C4H10)+ Н2O2 → 2CH3OH+ C2H4 +C3H6 + H2. It should be noted that other alcohols and other oxygen-containing products except methanol were not found in all presented experiments. The analysis of the liquid reaction products was carried out by chromatography in a specialized laboratory by the instruments LHM and "Tsvet 500" using the 3 m long nozzle "Polisorb". The analysis of experimental data led to the conclusion that direct conversion of propane (butane) into methanol allows to achieve the conversion level of 10% in one pass. The reactor design and the flow diagram of the laboratory setup for methanol synthesis by the cavitation method in the total absence of reaction byproducts were developed. The applied cavitation method is extremely promising for using propane-butane gas as a raw material in a fundamentally new production of methanol.